Lignosulfonates as Fire Retardants in Wood Flour-Based Particleboards - Stefania Angelini; Aitor Barrio; Pierfrancesco Cerruti; Gennaro Scarinzi; Javier Garcia-Jaca; Davide Savy; Alessandro Piccolo; Mario Malinconico (International Journal of Polymer Science)
Wood flour particleboards (WFP), like other wood-based items, require the addition of fire retardants (FRs) to reduce their high flammability. In this work, a waste lignosulfonate (CaLS) from paper mill is used as a low-cost FR to reduce WFP flammability. CaLS is purified by dialysis and the dialysed lignosulfonate (LD) is used, alone or combined with ammonium polyphosphate (APP), as a FR additive in the preparation of urea-formaldehyde WFP. The fire behaviour of the modified WFPs is studied by cone calorimetry. The use of 15 wt.% LD reduces the peak of heat release rate (HRR) and total smoke production by 25%, also increasing char formation. HRR peak is further reduced up to 40%, if APP is introduced in the formulation. This work discloses a viable and cost-effective strategy for improving the fire retardancy performance of WFP by partial replacement of a commercial FR with a fully renewable additive, isolated through a green and cost-effective process.